National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 10 Family doctor service 44. All doctors are to be entitled to take part in the new arrangements in the areas where they are already practising when the scheme begins. Taking part will not debar them from also continuing to make private arrangements for treating such people as still wish to be treated outside the service instead of taking advantage of the new arrangements, provided that such persons are not on their lists as public patients or on the lists of their partners in a Health Centre. People will be free to choose their own doctor (including their present doctor) subject to the doctor's consenting and being in a position to undertake their care. 45. All doctors taking part in this part of the new service will be in contract with the Executive Council for the area in which they practise. The Executive Council will be required to draw up and publish lists of all general practitioners who wish to participate. People will then choose their doctor and each doctor will have his own list of the people whom he has agreed to attend. There will be machinery for allocating among the doctors concerned such people as wish to take advantage of the service but have not chosen a doctor for themselves or have been refused by the doctor chosen by them. The relationship of the doctor with any person on his list — i.e., his functions under this part of the service — will then be similar to the ordinary relationship of doctor to patient as it is now known, except that the doctor's remuneration will come from public funds and not directly from the patient. 46. The Bill itself does not determine the detailed terms and conditions for doctors joining in the service or the doctors' remuneration. These are left to be settled by regulations and the necessary regulations will be made in consultation with the doctors' professional representatives. It is, however, the intention that remuneration should take the form of a combination of fixed part-salary and of capitation fees, the latter varying with the number of persons whose care is undertaken by each doctor and being so graduated as to diminish in scale as the total number of patients rises. Variations of the fixed part-salary will be possible so as to take account of different circumstances and experience and the differing conditions of practice in particular areas. It is intended also to institute, under powers contained in the Bill, a contributory superannuation scheme for doctors taking part in the new arrangements. 47. Actual rates of remuneration for doctors can be determined, in consultation with the profession, only after the report has been received of the Spens Committee — a special committee set up, by agreement with the profession's representatives and under the chairmanship of Sir Will Spens, with a membership half medical and half non-medical, to make an independent report on the appropriate range of remuneration for doctors taking part in a publicly organised service of this kind. 48. When the necessary regulations affecting terms of service and remuneration have been settled it will be for the Executive Councils to contract with the doctors on the lines thus prescribed. Distribution of medical practices 49. To help in dealing with the needs of under-doctored areas it is intended, as already indicated, to adjust the scales of remuneration of doctors so as to provide additional inducement to practise in less attractive areas. In addition, a new body to be called the Medical Practices Committee, mainly professional in composition, is to be appointed under the Bill to regulate in future the succession to old, or the opening of new, practices within the service. 292/847/4/115